An interactive booking-limit control for passenger railway revenue management. (December 2021) - Luo, Yongji; Yan, Haifeng; Zhang, Shoushuai
Abstract: Optimally rationing the number of seats sold among various products is a central problem in passenger railway revenue management. The most commonly used control for passenger railway in both practice and literature is partitioned booking-limit (PBL) control. However, PBL control will divide the train capacity into a number of small allocations if there are many products, leading to inefficiency when the booking demand has high randomness. Considering the deficiency of PBL control, this paper proposes a novel booking-limit control, namely interactive booking-limit (IBL) control, which can better deal with the problem of high demand randomness. The new control has two types of decision variables, i.e., the booking limit and the interactive factor. It is shown that PBL control is a special case of the proposed IBL control. A mathematical model of IBL control is formulated and a simulation-based stochastic approximation algorithm for the model is developed. The experimental results show that the solution algorithm can search an IBL solution that can bring more revenue than an optimal PBL solution within acceptable computing time. In addition, it is found that the revenue gap between the two solutions becomes larger when booking demand is highly stochastic. Highlights: An interactive booking-limit (IBL) control is proposed to enrich the family of passenger railway booking control strategies. Advanced seat reservation of passenger railway is considered in the modeling. Compared with partitioned control, the IBL control generates more revenue especially when demand is highly stochastic.